The implementation of Student Management In Improving the Competence of Graduates at SDN Karawang Kulon II - Iddah Fukhoiroh; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (Universitas Muhammadiyah Enrekang, 2022)
In Indonesia, the field of education is very important to learn, the purpose of this paper is to discuss improving the competence of graduate students. In the world of education, students are the main raw material in the process of science. Learning can be used as a supporting component that relates to one another. These components include educational objectives, materials, learning methods, and evaluation. From these several components, the teacher should take steps to choose and determine the approach or learning model. Now there are so many types of learning strategies or methods that aim to improve the competence of graduates so that they become better. The method used in this study uses a qualitative method, is a method used to examine the condition of a natural object where the researcher acts as a key instrument. Data collection techniques using literature study and interview techniques. The purpose of this paper is to determine the implementation of student management in improving the competence of graduates at SDN Karawang Kulon II.